Smart Admissions: Meningkatkan Efesiensi Proses Penerimaan Mahasiswa Baru dengan Chatbot Interaktif - Asmaul Husna RS; Adawiyah Asti Khalil; Mindi Richia Putri; Muhammad Ari Rifqi; Ari Kurniawati (Sekawan Institut, 2026)
The new student admission (PMB) process at the Baru Universitas Bima Internasional MFH often faces challenges related to time efficiency and administrative burdens due to repetitive inquiries from prospective students. This research aims to design and build an interactive chatbot system named